The history and philosophy of Islamization of knowledge: a preliminary study of pioneers' thought - Ali, Mohd Mumtaz (IIUM Press, 2019)
The 'Islamization of Knowledge' movement has given rise to serious debate among scholars about the nature of knowledge and education. This debate is clouded by several misunderstandings. The present work aims to clarify these misunderstandings by exploring the meaning, scope and methodology of Islamization of Knowledge. It deals with the term, concept, perception, principles and work plan of the movement.